Aging effects on pedicled fasciocutaneous flap survival in rats. (31st August 2015) - Roy, Sudeep; Aksamitiene, Edita; Hota, Salini; Zhang, Li‐Hui; Sciarrino, Joseph; Baker, Adam L.; Heffelfinger, Ryan N.; Tuluc, Madalina; Hoek, Jan B.; Pribitkin, Edmund A.
Abstract: Background: Poorer surgical outcomes in older patients undergoing locoregional head and neck reconstruction have raised questions about tolerance of aging tissue to iatrogenic ischemic insults. Methods: We examined the effects of aging on viability of pedicled composite flaps in 2‐month and 6‐month old Sprague–Dawley male rats and correlated flap survival with vascular endogenous growth factor (VEGF) and VEGF receptor 2‐mediated signaling events. Flap segments were assessed for gross/cellular necrosis by optical microscopy and for proangiogenic, apoptotic, and proliferative protein‐marker content. Results: Flap necrosis significantly increased with age (4.2% in young vs 49.17% in old), correlating with reduced expression of VEGF, inhibition of signal transducer and activator of transcription 3 (STAT3), and Akt activation, impaired Akt‐dependent endothelial nitric oxide synthase (eNOS) phosphorylation, elevated Bax/Bcl‐2 ratio, activation of Caspase‐3, upregulated nuclear poly (ADP‐ribose) polymerase‐1 (PARP‐1) cleavage and lower proliferating cell nuclear antigen (PCNA) levels. Conclusion: Pedicled flap survival is higher in younger rats in part because of unhindered expression of VEGF and enhanced activity of cell survival and promigratory signaling pathways. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1152–E1162, 2016